Stress state hoisting hooks - Казимов, Муса Исмаил оглы; Кулиев, Сабир Али оглы (Eastern-European Journal of Enterprise Technologies, 2015)
Stress state of the curved beam, the axis of which is drawn along a circular arc is considered. The beam is limited by the surfaces of the circular hollow cylinder. The cross-section of the beam can be of any shape (three different cross-sections, namely circular, rectangular and trapezoidal is taken as an example). The solution of the problem consists of three series of tasks: selecting the cross-section, approximate solution (based on the methods of strength of materials) and exact solution of the problem using the method of the theory of elasticity.